Penerapan Konsep Ijtihad dalam Mengatur Teknologi Reproduksi Modern di Indonesia - Nisa, Ihda Shofiyatun; Faizah, Isniyatin; Mashuri, Bisri; Khasanah, Muizzatul (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2025)
This study discusses the application of the concept of ijtihad in regulating modern reproductive technology in Indonesia using an Islamic law approach. The development of reproductive technologies such as in vitro fertilization (IVF), artificial insemination, and genetic engineering have raised various legal and ethical issues in Islam, particularly concerning the clarity of lineage (nasab), the legal status of children, and the validity of medical practices from a sharia perspective. Therefore, an in-depth analysis is needed to examine the role of ijtihad in establishing laws and regulations that align with Islamic principles. This research uses a normative legal research method with conceptual, legislative, and historical approaches. The data sources include primary legal materials such as the Qur’an, Hadith, and fatwas from the Indonesian Ulema Council (MUI), as well as national regulations governing reproductive technologies, such as the Health Law and other related regulations. In addition, secondary legal materials from Islamic law literature and academic studies are also analyzed to understand the legal development regarding reproductive technology practices in Indonesia. The results of the study indicate that the concept of ijtihad plays a strategic role in shaping fatwas and regulations related to modern reproductive technologies. MUI's fatwa permits IVF practices as long as they are performed by a legally married couple and prohibits the use of sperm or egg donors due to its contradiction with the principle of nasab in Islam. National regulations have also accommodated Sharia principles by limiting reproductive technology practices to avoid conflicts with religious norms. However, challenges in the implementation of these regulations remain, such as differences in interpretation among scholars, insufficient oversight of medical practices, and the low level of public understanding regarding Islamic law in reproductive technologies.